Chaotic dynamics of the size-dependent non-linear micro-beam model; Communications in Nonlinear Science and Numerical Simulation; Vol. 50 - Krysko A. V. Anton Vadimovich; Awrejcewicz J. Jan; Pavlov S. P.; Zhigalov M. V. Maksim; Krysko V. A. Vadim (2017, 2017)
Title screen